A Comparison of the Topside Electron Density Measured by the Swarm Satellites and Incoherent Scatter Radars Over Resolute Bay, Canada. Issue 11 (27th October 2021) - Larson, B.; Koustov, A. V.; Kouznetsov, A. F.; Lomidze, L.; Gillies, R. G.; Reimer, A. S.
Abstract: Electron density measured at high latitudes by the Swarm satellites is compared with the measurements by the RISR incoherent scatter radars as the satellites fly by the radars' field of views near Resolute Bay, Canada between 2014 and 2019. More than 200 satellite passes crossing multiple radar beams are considered. Overall, the Swarm‐based electron densities are smaller than those measured by the radars by ∼30%. The values are closer to one another at electron densities between ∼ 3 × 10 10 and ∼ 15 × 10 10 m − 3, corresponding to plasma frequencies between 1.5 and 3.5 MHz. Swarm‐measured values are getting progressively smaller than those measured by radars at larger electron densities/plasma frequencies. For the entire range of measured electron densities, the slope of the best fit linear line to the data expressed in terms of electron density is ∼0.62 and offset is ∼ 2 × 10 10 m − 3 . Stronger differences between the instruments were found for observations at nighttime and dawn. Plain Language Summary: In this article, electron densities measured by Langmuir Probes onboard Swarm satellites (∼450 km) are compared with electron densities measured by the incoherent scatter radars RISR‐N and RISR‐C over Resolute Bay, Canada. It is shown that the radars report larger electron densities than those reported by Swarm by 30%–35%. The differences are progressively larger at larger electron densities. Key Points: Swarm‐measured electron densities are smaller than those measured by incoherent scatter radars (ISR) radars at conjunctions by about 35% The linear fit line to Swarm vs. ISR electron density plots has a slope of ∼0.62 The effect of smaller Swarm electron densities is stronger at nighttime